The relationship of high-intensity cross-training with arterial stiffness - Jamie F. Burr; Jenny L. Beck; John J. Durocher (Elsevier, 2019)
Background: Central arterial stiffness is a cardiovascular risk factor that can be readily affected through engagement in physical exercise training, with resistance and aerobic exercise having disparate affects. Despite the growing popularity of high-intensity cross-training (HICT), little is currently known about the effects of this mixed modality exercise stimulus on arterial stiffness. Therefore, the purpose of this study was to characterize the arterial stiffness of habitual HICT participants vs. aerobically active and sedentary controls using a cross-sectional design. Methods: A total of 30 participants were recruited: 10 middle-aged long-term participants of HICT (CrossFit) and 20 age, sex, and height matched controls (10 recreationally active, 10 sedentary). Central and peripheral pulse wave velocities were measured for the carotid-femoral and femoral-dorsalis pedis arterial segments. Aerobic fitness (maximal oxygen uptake, VO2max) was measured and typical exercise participation rates were self-reported for each group. Results: HICT participants manifested central pulse wave velocity (PWV) (5.3 ± 1.0 m/s, mean ± SD) and VO2max (43 ± 6 mL/kg/min) values nearly identical to active controls. Both active groups had significantly better values than sedentary controls (7.1 ± 1.0 m/s, p ≤ 0.001; and 32 ± 7 mL/kg/min, p = 0.01). No differences were observed in peripheral PWV between groups. Conclusion: Habitual participation in HICT exercise was not associated with increased central nor peripheral arterial stiffness. Long-term HICT participants presented with similar fitness and arterial stiffness as compared with participants who practiced traditional aerobic exercise. Compared to sedentary living, HICT may offer musculoskeletal and cardiovascular health benefits without negatively impacting arterial stiffness. Keywords: Circuit training, CrossFit, Pulse wave velocity, Resistance exercise, Vascular, Weight training